Efek Carburizing Terhadap Sifat Mekanik Limbah Drum Oli sebagai Bahan Baku di Industri Kecil Pande Besi - Hadi Darmo, Adityo Noor Setyo; Listyanda, Faiz; Hayati, Nur (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
Oil drum waste, cheap but not yet optimally utilized. This waste has the potential to be a substitute for carbon steel base material for making metal crafts through heat treatment. This research aims to determine the effectiveness of the influence of beef bone and barium carbonate as an energizer on the sharpness of coconut shell charcoal carbon diffusion into used oil drum waste after the pack carburizing process. The used drum test specimen with a content of 0.0379% C, was placed in a carburizer environment of coconut shell charcoal powder mixed with 20%, 25%, and 30% beef bone meal energizer and 20% barium carbonate (BaCO3) heated at a temperature of 800 0C, 850 0C and 900 0C with a holding time of 30 minutes immediately quenched. The effectiveness of carbon diffusion and macro structure were evaluated using a